Comparative study of modified vs. traditional sacroiliac screw techniques in day type II crescent fracture dislocation of the pelvis - Li, Renjie; Wang, Xiaopan; Liu, Leyu; Guan, Jianzhong; Zhao, Peishuai; Chen, Xiaotian; Wu, Min (Frontiers in Surgery, 2025)
BackgroundThe use of traditional sacroiliac screws in the treatment of Day type II crescent fracture-dislocation of the pelvis (CFDP) is often associated with insufficient screw anchorage and compression due to the short iliac segment of the screw and the proximity of the entry point to the fracture line. This study aims to evaluate a modified sacroiliac screw technique designed to address these limitations.MethodsIn this retrospective comparative study, we analyzed 44 patients with Day type II CFDP who underwent surgical treatment between January 2019 and June 2023. Based on the sacroiliac screw technique applied, patients were divided into a modified group (n = 21) and a control group (n = 23). We compared the sacroiliac screw-related metrics, the quality of reduction assessed by Matta score, and clinical outcomes evaluated using the Majeed functional score and the visual analogue scale (VAS) for pain.ResultsAll patients successfully underwent surgery. The modified group exhibited a significantly longer iliac segment of the sacroiliac screw compared to the control group (3.71 ± 0.85 cm vs. 2.12 ± 0.47 cm, P < 0.001). The distance from the screw entry point to the iliac fracture line was greater in the modified group (3.31 ± 0.88 cm vs. 1.22 ± 0.64 cm, P < 0.001). Reduction quality assessed by Matta score one week postoperatively was superior in the modified group: excellent in 12, good in 7, fair in 2, and poor in 0 cases; vs. excellent in 6, good in 12, fair in 5, and poor in 0 cases in the control group (P < 0.05). At the final follow-up, the modified group showed better VAS scores for sacroiliac joint pain than the control group (P < 0.05). No significant difference was observed in Majeed functional scores between the two groups (P = 0.568).ConclusionThe modified sacroiliac screw technique significantly extends the iliac segment length, enhances cortical bone engagement, reduces the risk of entry point proximity to the fracture line, and improves screw stability and reduction quality. However, these findings require validation through larger prospective and biomechanical studies to further assess long-term efficacy and applicability.